2020
DOI: 10.1177/0081246320963204
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and academic failure among first-year university students in South Africa

Abstract: Universities in South Africa face ongoing challenges with low rates of academic attainment and high rates of attrition. Our aims were to (1) investigate the extent to which common mental disorders evaluated early in the first year predict academic failure at the end of the year, controlling for sociodemographic factors and (2) establish the potential reduction in prevalence of failure that could be achieved by effectively treating associated mental disorders. Self-report data were collected from first-year stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
4
20
0
2
Order By: Relevance
“…Mental illness is a public health priority, affecting as much as 47% of the population at some point in their lifetime [1]. Literature has identified university students as a group that is particularly vulnerable to mental illness [2][3][4][5][6]. A review on depression among university students reported that depression prevalence ranged between 6 and 54% among university students [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental illness is a public health priority, affecting as much as 47% of the population at some point in their lifetime [1]. Literature has identified university students as a group that is particularly vulnerable to mental illness [2][3][4][5][6]. A review on depression among university students reported that depression prevalence ranged between 6 and 54% among university students [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these traditional determinants, research has begun to explore the contribution of well-being, including mental health, as a potential contributor to student academic performance. This emerging research suggests that university students suffering from common mental disorders, especially anxiety and depression, are likely to perform poorly when compared to students without mental disorders [2,3,18]. A study among university students in the United States of America (USA), found that depression was not only linked to a lower grade point average (GPA), but also an increased likelihood of attrition [2].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the experiences of trauma measured in this study, life in higher education and the associated academic pressures are stressful and impact mental wellbeing amongst female students [11,28]. These impacts have since been compounded by the COVID-19 pandemic, including the changes in the teaching and learning models that needed to be adopted [59].…”
Section: Discussionmentioning
confidence: 88%
“…Academic stressors, intimate relationship problems, and recent breakups were also associated with students' depressive symptoms [26]. Depressive symptoms and frequent binge drinking were also associated with poor academic performance and failure [28].…”
Section: Introductionmentioning
confidence: 97%
“…16 Our earlier work in South Africa suggested that providing effective treatment to first-year students with major depressive disorder and/or attention deficit hyperactivity disorder could yield a 23.0% proportional reduction in prevalence of academic failure, highlighting the importance of promoting mental health as a strategy for raising educational attainment. 17 There has been a marked increase in the incidence of depressive and anxiety disorders following the outbreak of COVID-19 in both the general population and among university students. An analysis of the best available global survey data with measurements of anxiety and depression both before and during the pandemic, using the Global Burden of Disease Study model, estimated an additional 53.2 million cases of depressive disorder and 76.2 million cases of anxiety disorder globally (equivalent to a 27.6% increase in depression and a 25.6% increase in anxiety disorders).…”
Section: Introductionmentioning
confidence: 99%